Tissue Transglutaminase Is an Essential Participant in the Epidermal Growth Factor-stimulated Signaling Pathway Leading to Cancer Cell Migration and Invasion - Antonyak, Marc A.; Li, Bo; Regan, Andrew D.; Feng, Qiyu; Dusaban, Stephanie S.; Cerione, Richard A. (The Journal of biological chemistry, 2009)
Epidermal growth factor (EGF) exerts pleiotropic effects during oncogenesis, including the stimulation of cell migration and invasiveness. Although a number of traditional signaling proteins (e.g. Ras and Rho GTPases) have been implicated in EGF-stimulated cancer cell migration, less is known about the identity of those proteins functioning further downstream in this growth factor pathway. Here we have used HeLa carcinoma cells as a model system for investigating the role of tissue transglutaminase (TGase), a protein that has been linked to oncogenesis, in EGF-stimulated cancer cell migration and invasion. Treatment of HeLa cells with EGF resulted in TGase activation and its accumulation at their leading edges, whereas knocking down TGase expression, or treating cells with a TGase inhibitor, blocked EGF-stimulated cell migration and invasion. We show that EGF signaling through Ras and c-Jun N-terminal kinase is responsible for targeting TGase to the leading edges of cells and activating it. The requirement for EGF to properly localize and activate TGase can be circumvented by the expression of oncogenic Ras (G12V), whose ability to stimulate migration is also dependent on TGase. We further show that, in the highly aggressive breast cancer cell line MDAMB231, where EGF stimulation is unnecessary for migration and invasive activity, TGase is already at the leading edge and activated. These findings demonstrate that TGase plays a key role in cancer cell motility and invasiveness and represents a previously unappreciated participant in the EGF pathway that stimulates these processes in cancer cells.